Going beyond metaphtonymy: Metaphoric and metonymic complexes in phrasal verb interpretation - lvalue lvalue (Universitat Jaume I. Department of English Studies, 2019)
Author/s Francisco José Ruiz de Mendoza Ibáñez Alicia Galera-Masegosa University of La Rioja, Spain   ABSTRACT A metaphor can combine with another metaphor, or a metonymy with another metonymy, into a single meaning unit, thus giving rise to either a metaphorical or a metonymic amalgam. The combination of a metaphor and a metonymy, as discussed in Goossens (1990) and Ruiz de Mendoza and Díez (2002), gives rise to so-called "metaphtonymy". Amalgams and metaphtonymy are cases of conceptual complexes. Several such complexes have been identified in previous studies (e.g. Ruiz de Mendoza and Díez 2002, Ruiz de Mendoza and Mairal 2011). Here we revisit such studies and postulate the existence of metaphoric chains as an additional case of metaphoric complex in connection to the semantic analysis of phrasal verbs. Metaphoric chains, unlike amalgams (Ruiz de Mendoza and Mairal 2011), do not involve integrating the conceptual structure of the combined metaphors. Instead, metaphoric chains involve a mapping sequence in which the target domain of a first metaphoric mapping constitutes the source domain of a subsequent metaphor.